2012
DOI: 10.1111/j.1600-6143.2011.03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes from BENEFIT, a Randomized, Active-Controlled, Parallel-Group Study in Adult Kidney Transplant Recipients

Abstract: The clinical profile of belatacept in kidney transplant recipients was evaluated to determine if earlier results in the BENEFIT study were sustained at 3 years. BENEFIT is a randomized 3 year, phase III study in adults receiving a kidney transplant from a living or standard criteria deceased donor. Patients were randomized to a more ( Belatacept-treated patients maintained a high rate of patient and graft survival that was comparable to cyclosporine-treated patients, despite an early increased occurrence of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
228
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(248 citation statements)
references
References 34 publications
17
228
0
1
Order By: Relevance
“…These findings are consistent with analyses performed at 3 years posttransplant,12, 13 which suggests that the effects of belatacept on preventing de novo DSA development are sustained over time. In the subset of patients in BENEFIT and BENEFIT‐EXT who developed de novo DSAs, belatacept‐based treatment appeared to result in lower antibody titers compared with cyclosporine‐based treatment.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with analyses performed at 3 years posttransplant,12, 13 which suggests that the effects of belatacept on preventing de novo DSA development are sustained over time. In the subset of patients in BENEFIT and BENEFIT‐EXT who developed de novo DSAs, belatacept‐based treatment appeared to result in lower antibody titers compared with cyclosporine‐based treatment.…”
Section: Discussionsupporting
confidence: 88%
“…14 It is noteworthy to differentiate our results from the belatacept phase III trial, which showed higher rates of early endarteritis (18% versus 4%) and slightly less DSA (4% versus 7%) but superior renal function and comparable graft survival through 5 years in patients treated with belatacept versus cyclosporin, respectively. [24][25][26] Another study indicated that patients treated with belatacept had more T-regulatory cells in biopsies during rejection compared with patients treated with calcineurin inhibitor, 27 suggesting that belatacept may ease recovery from acute rejection by selective immune regulation. In contrast, most patients in our cohort were on calcineurin inhibitors, and endarteritis unresponsive to anti-T cell therapy was a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…BENEFIT-extended criteria donor transplant recipients (BENEFIT-EXT) was similar to BENEFIT, except for the use of extended criteria donors. Despite higher rates of early acute rejection (AR) compared with patients treated with CsA, patients treated with belatacept had superior allograft function (higher calculated GFR [cGFR]) at 1 year that was sustained over 3 years, with equivalent patient and graft survival (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Belatacept, which is now approved for use in adult renal transplant patients, has been compared with a CNI-based regimen using cyclosporine (CsA) in Phase 3 trials (6)(7)(8)(9). The Belatacept Evaluation of Nephroprotection and Efficacy as First-Line Immunosuppression Trial (BENEFIT) was a 3-year, multicenter, randomized, prospective study that included 666 adult kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 99%